+0  
 
0
74
3
avatar

\({(6 \sqrt [3] {2} -4{\sqrt{13})}^{2} }\)

Guest Sep 24, 2017
Sort: 

3+0 Answers

 #1
avatar+79654 
+1

( 6∛2 - 4√13)^2  =

 

( 6∛2 - 4√13) ( 6∛2 - 4√13)  =

 

36∛4 - 24*√13*∛2 - 24*√13*∛2 + 16*13 ) =

 

36∛4 - 48*√13*∛2 + 208

 

 

 

cool cool cool

CPhill  Sep 24, 2017
 #2
avatar
0

how'd you get 208 ?

Guest Sep 25, 2017
 #3
avatar+5541 
+1

When you multiply the "last" terms, you get.....

 

-4√13 * -4√13   =   16 * √13 * √13   =   16 * √132   =   16 * 13   =   208

hectictar  Sep 25, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details